Agricultural extension in Cambodia: An assessment and options for reform - Ke, Sam Oeurn; Babu, Suresh Chandra (International Food Policy Research Institute, 2018)
This paper assesses the performance of Cambodia’s agriculture extension system, identifies challenges and analyzes constraints and opportunities for that system, and finally identifies actions needed to improve the extension system. We offer recommendations for both policy makers and practitioners regarding the current status of extension in Cambodia.